Nicoletta Simone: capstone - Simone, Nicoletta, artist (Colorado State University. Libraries, 2017)
The artist's statement: As an Italian-American who grew up in Italy and is now living in the United States, my work deals with the challenge of balancing between cultures. Of feeling unrecognized but also having to prove culture. In my work I am attempting to address this push and pull. The way immigration increases bonds in a community by redefining traditions and values while at the same time doing the opposite. I am also curious about the role of technology in globalization. I address these issues through process-based work like layered projected drawings of synchronized swimmers in the hope of disorienting the viewers in the same way that culture can be disorienting. Language acquisition is a huge factor in immigrant experience and I like how horizontal mark making seems to imitate the process of writing. I am particularly interested in the commonality of experiences in relation to learning language.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
Video has no sound.